Islam in the Malay World: A marginal or significant influence? - Zakariya, Hafiz (2018)
This presentation first discusses the meaning of Malay and the Malay world. Second, it examines the origins and migrations of the Malays. Third, it demonstrates the marginalization of Islam in the Malay word in Islamic studies and Orientalist misrepresentations of Islam in Southeast Asia. Fourth, it discusses the impacts of Islam on Malay Society by probing the classical orientalist and Naquib al-Attas’ viewpoints. In doing so, it finds a middle ground between the opposing perspectives. Finally, it discusses the unique characteristics of Islam in the Malay World, distinguishing it from Islam in west Asia.